A Critical Review of The Attempts to Represent The Law and The Legal Reasoning Process in Computer Programmes - Ponnu, Cyril H. (Malaysian Journal of Computer Science, 1996)
Evaluates some of the previous attempts to represent the law and the legal reasoning process in computer programmes. It examines previous work in the area to demonstrate that researchers have generally ignored the complexity of the law and the legal reasoning process and have tended to focus on very narrow aspects of the law and legal reasoning process. The aim here is to highlight the limitations of the various approaches given that the nature of law and legal reasoning is such that it presents severe obstacles to those who undertake to represent the law and legal reasoning within a computer programme.